Youth perceptions of alcohol advertising: Are current advertising regulations working? - Aiken, A.; Lam, Tina; Gilmore, William; Burns, L.; Chikritzhs, Tanya; Lenton, Simon; Lloyd, B.; Lubman, D.; Ogeil, R.; Allsop, S. (Wiley-Blackwell Publishing Asia, 2018)
Objectives: We investigated young people's exposure to alcohol advertising, their intentions to consume and purchase alcohol products following the viewing of advertisements, and whether they perceived the actors in the advertisements as being under the age of 25 years. Methods: Face-to-face interviews were completed with 351 risky drinking 16-19-year-old Australians, with a sub-sample (n=68) responding to a range of alcohol advertisements in an in-depth interview. Results: Participants were exposed to alcohol advertisements from an average of seven specific contexts in the past 12 months, with younger adolescents more likely to recall TV and outdoor billboards (n=351). Positive perception of advertisements was associated with increased intention to use and to purchase advertised products (n=68). A liqueur advertisement actor was perceived by 94% as being under 25 years-old, and almost 30% thought the advertisement was marketed at people younger than 18 years of age. Conclusions: Young people's perceptions of alcohol advertising are not necessarily in line with expert/industry assessment; products are sometimes marketed in a way that is highly appealing to young people. Greater appeal was associated with increased intention to consume and to purchase products. Implications for public health: These results indicate deficiencies in the effectiveness of current advertising codes in regard to protecting the health and wellbeing of adolescents.